Germline SAMD9L truncation variants trigger global translational repression. - Allenspach, Eric J; Soveg, Frank; Finn, Laura S; So, Lomon; Gorman, Jacquelyn A; Rosen, Aaron B I; Skoda-Smith, Suzanne; Wheeler, Marsha M; Barrow, Kaitlyn A; Rich, Lucille M; Debley, Jason S; Bamshad, Michael J; et al. (J Exp Med, 2021)
SAMD9L is an interferon-induced tumor suppressor implicated in a spectrum of multisystem disorders, including risk for myeloid malignancies and immune deficiency. We identified a heterozygous de novo frameshift variant in SAMD9L in an infant with B cell aplasia and clinical autoinflammatory features who died from respiratory failure with chronic rhinovirus infection. Autopsy demonstrated absent bone marrow and peripheral B cells as well as selective loss of Langerhans and Purkinje cells. The frameshift variant led to expression of a truncated protein with interferon treatment. This protein exhibited a gain-of-function phenotype, resulting in interference in global protein synthesis via inhibition of translational elongation. Using a mutational scan, we identified a region within SAMD9L where stop-gain variants trigger a similar translational arrest. SAMD9L variants that globally suppress translation had no effect or increased mRNA transcription. The complex-reported phenotype likely reflects lineage-dominant sensitivities to this translation block. Taken together, our findings indicate that interferon-triggered SAMD9L gain-of-function variants globally suppress translation.

Multiplexed Functional Assessment of Genetic Variants in CARD11. - Meitlis, Iana; Allenspach, Eric J; Bauman, Bradly M; Phan, Isabelle Q; Dabbah, Gina; Schmitt, Erica G; Camp, Nathan D; Torgerson, Troy R; Nickerson, Deborah A; Bamshad, Michael J; Hagin, David; Luthers, Christopher R; et al. (Am J Hum Genet, 2020)
Genetic testing has increased the number of variants identified in disease genes, but the diagnostic utility is limited by lack of understanding variant function. CARD11 encodes an adaptor protein that expresses dominant-negative and gain-of-function variants associated with distinct immunodeficiencies. Here, we used a "cloning-free" saturation genome editing approach in a diploid cell line to simultaneously score 2,542 variants for decreased or increased function in the region of CARD11 associated with immunodeficiency. We also described an exon-skipping mechanism for CARD11 dominant-negative activity. The classification of reported clinical variants was sensitive (94.6%) and specific (88.9%), which rendered the data immediately useful for interpretation of seven coding and splicing variants implicated in immunodeficiency found in our clinic. This approach is generalizable for variant interpretation in many other clinically actionable genes, in any relevant cell type.
Keywords: Adenine; B-Cell CLL-Lymphoma 10 Protein; B-Lymphocytes; CARD Signaling Adaptor Proteins; Cell Line; Diploidy; Exons; Genes, Dominant; Genetic Variation; Guanylate Cyclase; Humans; Immunologic Deficiency Syndromes; Jurkat Cells; Lymphoma; NF-kappa B p50 Subunit; Piperidines; Polymorphism, Single Nucleotide; Primary Immunodeficiency Diseases; Sensitivity and Specificity